2021
DOI: 10.1001/jamaophthalmol.2020.4749
|View full text |Cite
|
Sign up to set email alerts
|

Association of Patterns of Glaucomatous Macular Damage With Contrast Sensitivity and Facial Recognition in Patients With Glaucoma

Abstract: IMPORTANCEFacial recognition is a critical activity of daily living that relies on macular function. Glaucomatous macular damage may result in impaired facial recognition that may negatively affect patient quality of life.OBJECTIVE To evaluate the association of patterns of glaucomatous macular damage with contrast sensitivity and facial recognition among patients with glaucoma. DESIGN, SETTING, AND PARTICIPANTSIn this prospective cohort study at a single tertiary care center, 144 eyes of 72 consecutive patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…It has been recognized that the use of regional correlations may improve the understanding of progression in both glaucoma subtypes. Hood and colleagues looked closely at RGCs within the macula along with the 10-2 VF test and described 2 patterns of macular damage: focal and/or diffuse 48. These 2 patterns of macular damage are best differentiated by comparing abnormal regions on the 10-2 VF with the corresponding regions on RGCs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recognized that the use of regional correlations may improve the understanding of progression in both glaucoma subtypes. Hood and colleagues looked closely at RGCs within the macula along with the 10-2 VF test and described 2 patterns of macular damage: focal and/or diffuse 48. These 2 patterns of macular damage are best differentiated by comparing abnormal regions on the 10-2 VF with the corresponding regions on RGCs.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also suggests that diffuse rather than focal structural macular damage in the better seeing eye may be associated with diminished facial recognition, although this will need to be validated in future studies with larger sample sizes. These findings generally support previous work showing functional differences between patients with diffuse and focal macular damage . It also suggests that the global effect of diffuse damage appears to result in worsened visual function.…”
Section: Discussionmentioning
confidence: 99%
“…People with vision impairment report difficulties with both discrimination of familiar faces and recognition of facial expressions under a range of conditions, with potential to cause anxiety, embarrassment, avoidance of social situations and social isolation 1–4 . Studies have shown that ocular conditions affecting central or peripheral vision can cause reduced performance on various face recognition tasks, 5–18 and that both impaired visual acuity (VA) and contrast sensitivity (CS) are associated with poor face recognition 5–11 . Although most previous studies have investigated the relationship between vision impairment and face recognition under photopic conditions, people with vision impairment also report difficulties with face recognition under low luminance conditions, such as seeing faces in a dim restaurant 19 …”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that, compared to age‐similar adults without ocular disease, both photopic discrimination of facial identity and recognition of facial expressions are reduced for patients with age‐related macular degeneration (AMD) 5–9,12–14 and glaucoma 10,12,15–18 . Furthermore, poorer discrimination of facial identity and poorer recognition of facial expressions under photopic conditions have been associated with greater disease severity and vision loss.…”
Section: Introductionmentioning
confidence: 99%